Onction des malades, funérailles et commémorations : pour une histoire des textes et des pratiques liturgiques en Éthiopie chrétienne - Anaïs Wion (Afriques)
During what historical contexts did the liturgical texts for accompanying a Christian into the hereafter become part of the Ethiopian Orthodox corpus? Two texts govern the sacrament for anointing the sick. The Mashafa Bāhry (Book of substance), which belongs to a set of normative texts copied during Zar’a Yā’eqob’s rule (1434-1468), proposes an overview of apostolic traditions. The Mashafa Qandil (Book of the lamp), a translation of the Coptic ritual observed during the reign of King Galāwdēwos (1540-1554), followed a century later. It apparently did not supplant its predecessor, given the number of copies made; but a printed version of it came out in the 20th century. The collection Mashafa Genzat (Book of burial) governs the rituals related to funerals and memorial services. After describing the successive forms assumed by this collection, questions are raised about the links between these texts and ritual practices, and about the place of “magic” in relation to the hereafter. The prayers in the widely used collection known as the Lefafā Sedeq are grounded in conceptions of magic about the power of intercession through prayer for the salvation of souls.